THE INDIVIDUAL ANTIGENIC SPECIFICITY OF ANTIBODIES TO STREPTOCOCCAL CARBOHYDRATES - Braun, Dietmar G. (The Rockefeller University Press, 1968)
Although a single electrophoretically uniform antibody component with specificity for the group carbohydrate may comprise the bulk of the γ-globulin in rabbits immunized with streptococcal vaccines, this is not always the case. Not infrequently, electrophoresis may reveal multiple antibody components. Nevertheless, it has been feasible by various preparative procedures to isolate from a single antiserum at least two antibody components with similar reactivity for the carbohydrate both of which are electrophoretically monodisperse. Light chains from such antibodies reveal a restricted pattern when examined by disc electrophoresis. Antibodies to streptococcal carbohydrates have been examined for their individual antigenic specificity. Goats were immunized with isolated Group C and Group A-variant antibodies raised in rabbits. Individual antigenic specificity of these antibodies was brought out by absorption of the goat anti-antiserum with Fr II of pooled normal rabbit sera. Additional absorption of the goat anti-antisera with Fr II diminished but did not eliminate the reactivity for the homologous antibody. Immunoelectrophoretic studies with papain fragments of purified streptococcal antibodies localized the specificity to the Fab fragment. Specificity was not confined to the isolated light chains of the antibody.